Holocene mountain glacier history in the Sukkertoppen Iskappe area, southwest Greenland. (1st October 2018) - Schweinsberg, Avriel D.; Briner, Jason P.; Miller, Gifford H.; Lifton, Nathaniel A.; Bennike, Ole; Graham, Brandon L.
Abstract: Mountain glaciers and ice caps (GIC) independent of the Greenland Ice Sheet respond rapidly to climate variations and records of their past extent provide information on the natural envelope of climate variability. Here, we use a multi-proxy approach that combines proglacial lake sediment analysis, cosmogenic nuclide surface-exposure dating ( in situ 10 Be and 14 C), and radiocarbon dating of recently ice-entombed moss to generate a centennial-scale record of Holocene GIC fluctuations in southwestern Greenland. Following local deglaciation ∼10-9 ka, sediments from proglacial Crash Lake record a glacier advance at ∼9 ka that is indistinguishable from nearby ice sheet moraines, implying a synchronous response of GIC and the Greenland Ice Sheet to a centennial-scale climate event. Following this local glacier advance, GIC experienced net recession until ∼4.6 ka. Radiocarbon ages of in situ moss ( n  = 29) and Crash Lake sediments reveal intervals of glacier expansion at ∼1.8, 1.2 and 0.7 ka that are superimposed on an overall trend of net glacier expansion throughout the late Holocene. In situ 14 C concentrations from bedrock adjacent to radiocarbon-dated moss samples further constrain the duration of ice cover through the Holocene in this region. We find that our glacier-size proxy records during the past ∼4 ka are broadly consistent with relatively lower temperatures recorded in GISP2 and occur during, or following, intervals of volcanic perturbations. Thus, we speculate that volcanic activity, although less frequent and intense than in the early Holocene and during the Little Ice Age, may have led to centennial-scale variability imprinted on net glacier expansion due to decreasing summer insolation through the late Holocene. Highlights: Multiple proxies record Holocene local glacier fluctuations in southwest Greenland. Local glaciers advanced synchronously with the Greenland Ice Sheet margin at ∼9 ka. Glacier regrowth at 4.6 ka with successive glacier expansion at 1.8, 1.2 and 0.7 ka. Late Holocene glacier advances are coeval with reduced temperatures and increased sea ice.